Analysis of Web Application Security - Jewliya, Shreekishan (International Journal of Computer Sciences and Engineering, 2025)
Web applications are a standout amongst the most predominant stages for data and administrations conveyance over Internet today. As they are progressively utilized for basic administrations, web applications turn into a prominent and significant focus for security assaults. Despite the fact that a huge group of methods have been developed to invigorate web applications and alleviate the assaults toward web applications, there is little exertion gave to drawing associations among these strategies and building a major picture of web application security look into. This paper reviews the range of web application security, with the point of systematizing the current strategies into a enormous picture that advances future research. We initially present the one of kind viewpoints in the web application advancement which brings inalienable difficulties for building secure web applications. At that point we distinguish three fundamental security properties that a web application should protect: Input Validity, State Integrity what's more, Logic Correctness, and depict the relating vulnerabilities that abuse these properties alongside the assault vectors that adventure these vulnerabilities. We compose the current research works on securing web applications into three classifications in view of their outline theory: security by Construction, security by Verification and security by Protection. At long last, we compress the lessons learnt and examine future research openings around there.